Nutrient mass balance for improved traditional coastal shrimp ponds of Bangladesh - Barua, P.; Zamal , H.; Chowdhury, M.S.N. (Mesopotamian Journal of Marine Sciences, 2022)
Three category of tidal water exchange system depended ponds have been selected for the experiments which were canal connected, river connected and pond connected pond. Present study was undertaken to estimate the nutrient balance into the coastal shrimp ponds of Cox’s Bazar coastal region. It was found that mineral fertilizer, organic fertilizer, feed, fish and shrimp fry, water supply and rainfall are the nutrient input and crop product (fish, shrimp, crab), crop residues, denitrification, water discharge and sedimentation are the nutrient output for shrimp pond. Estimation of overall nutrient mass balance per hector basis indicates that fertilizer was the highest nutrient contributor as followed by the supplementary feed into the experimental ponds. The total inputs of nitrogen and phosphorus were 78.87 kgha-1cycle-1 and 42.85 kgha-1cycle-1 respectively. Among the input only 34.6 % of nitrogen and 7.20 % of phosphorus were removed as harvested shrimp, fish and crab. A large portion, 38.58 % of N and 91.38 % of P were remained in the sediments and unaccounted for. From the investigation on nutrient balance for 3 categories of shrimp ponds it was concluded that Reuse water or pond connected pond system for coastal shrimp ponds should not be practiced anywhere in Bangladesh